PEMAKAIAN ORGAN DAN TISU BINATANG: KESANNYA TERHADAP IBADAT SOLAT - Muda, Zulkifli (Jurnal Syariah, 2019)
With the remarkable progress of medication nowadays, many diseases can be cured. The example of the progress is the replacement of human organ/tissue in human body by animal organ/tissue. It is to be noted that in every muslims' ibadah especially solat, everything should be clean and pure. If not it will render the solah invalid. This article will examine the effect of the validity of solat due to the use of animal organ and tissue in human body.